Chemical characterization of South American red wines - Valentin, Leonardo Antonio (2019)
In this study, 83 wines considered by experts as representatives of the following commercial categories: \"Argentinean Malbec (AM)\", \"Brazilian Merlot (BM)\", \"Uruguayan Tannat (UT)\" and \"Chilean Carménère (CC)\" were analyzed according to their composition of phenolic, volatiles and semi-volatiles compounds. The objective was to identify the chemical compounds profile that characterized each commercial category. From about 600 peaks obtained by chromatographic techniques, 169 were identified and 53 of them were selected for multivariate statistical analysis. Four clusters, designated as \"Chemical Categories\" were obtained. Chemical Category 2 and Chemical Category 4 were composed by 90% of CC and 68% of AM respectively, Chemical Category 3 grouped mostly CC (50%) and BM (36%), while Chemical Category 1 showed predominance of AM (37%) and UT (30%). Based on the chemical classification, CC wines were characterized by higher content of Isopentyl lactate, Isobutyl alcohol, Ionone, malvidin and gallic acid and lower content of rutin, quercetin and resveratrol. On the other side, AM wines showed higher concentration of myricetin. UT wines had the highest antioxidant activity, higher content of quercetin, epicatechin, rutin and also the highest amount of all semi-volatiles detected in the negative mode, while BM wines only showed the highest concentration of catechin, petunidin and all semi-volatiles detected in the positive mode. Considering that phenolic and volatile compounds are strictly associated to the wines sensory characteristics, these data can contribute to establish criteria for further wines authentication and typification.